PENCIPTAAN BUKU ILUSTRASI REGALIA KERATON NGAYOGYAKARTA HADININGRAT SEBAGAI UPAYA PENGENALAN FILOSOFI KEPEMIMPINAN JAWA KEPADA REMAJA - Permadi, Dimas Nugroho Azis; Fianto, Achmad Yanu Alif; Fahminnansih, Fenty (Jurnal Art Nouveau, 2015)
Abstract: The creation of an illustrated book based media form as a depiction of local wisdom contained in Regalia Keraton Ngayogyakarta Hadiningrat is a study that aims to introduce the philosophy of Java to youth leadership. By using descriptive qualitative analysis method The processed data from interviews, observation and literature, drawn a conclusion that is used as the concept of creation. The concept of creation found is "Modeling the Great Coat", which represent the value of the concept of culture behind Regalia Keraton Ngayogyakarta Hadiningrat which has been less exposed. Because, at this time the teens are more interested in things that are modern and quickly bored in reading. The Java philosophy of leadership is on heirloom Keraton Ngayogyakarta Hadiningrat called Regalia. There are eight types of Regalia namely Banyak, Dhalang, Sawung, Galing, Hardawalika, Kutuk, Kacu Mas, and Kandhil. Meanwhile, cultural preservation should and must to be done. Moreover, many lessons can be taken in the values and philosophy that can be applied to the social life of todays society. The use of illustrations to depict cultural values in the Regalia Keraton Ngayogyakarta Hadiningrat, giving new nuances in an effort to introduce the leadership philosophy of Java.Â Keywords: Creation , Illustration , Regalia Keraton Ngayogyakarta Hadiningrat